Weighted Energy-Balanced Efficient Routing Algorithm for Wireless Body Area Network. (16th February 2016) - Li, Zhuoming; Xu, Zhenyu; Mao, Shengge; Tong, Xing; Sha, Xuejun
Abstract : Wireless Body Area Network (WBAN) is a small-scaled sensor network consisting of a series of medical devices attributed to, around, or implanted in a human body, providing continuous monitoring by different sensors to collect vital signals or motion and GPS. This paper proposes an effective routing algorithm to balance the energy consumption within a WBAN in order to prolong the overall lifetime of the network, called dynamic routing algorithm (DRA) and its improved version based on a multipath choice mechanism. Theoretical analysis and simulation result are demonstrated to evaluate the performance of the algorithm and represent that energy consumption of sensors in the network is reasonably scheduled and life cycle of the network is significantly extended. The routing algorithm proposed in this paper may be potentially applied to significantly save energy of multiple types of sensors during vital signals aggregating and transmitting under the WBAN.